Investigating the uncertain nature of the supply chain when outsourcing and the impacts of Information Technology System on managing uncertainties - Liu, Yibin (2008)
This paper covered three main topics in supply chain management studies: outsourcing, supply chain uncertainty and Information Technology (IT) system. The survey revealed that the outsourcing practices of participating companies are still mainly focusing on cost factors, which might mislead the managerial focus to the wrong direction and cause unnecessary uncertainties within the supply chain. The survey also indicates the fact that advanced IT communication system, such as internet, intranet, extranet are not well utilised, while the traditional methods of communication, such as telephone, fax and post are still popular. In addition, the IT systems of participating companies were performed at the averagely acceptable level, despite some concerning issues of cost and flexibility. Three major implications of IT system on managing supply chain uncertainties can be summarised: IT can smooth information flow and increase informative visibility; improve flexibility and reduce order cycle time; and synergise the whole supply chain with integrated IT system and commonly shared database.